Evaluasi Program Pembelajaran Literasi Multibahasa di Sekolah Dasar - Wulandari Arifin, Nita; Nurul Hidayah, Aida (Papanda Publisher, 2023)
This research aims to evaluate the multilingual literacy learning program at SDN Ciborelang I. The research method used is a qualitative approach with phenomenological research design. Data were collected through interviews, classroom observations, and document analysis. The results of data analysis showed a significant improvement in students' multilingual literacy skills after participating in the program. These findings support previous research findings on the effectiveness of multilingual learning programs in improving students' language skills. Practical implications include the importance of developing inclusive curricula, providing ongoing teacher training, and involving parents and communities in supporting multilingual learning programs. Recommendations for future research include the development of new learning methods and deeper program evaluations. By implementing these steps, it is hoped that multilingual literacy learning programs can become more effective in preparing students to meet the demands of globalization and become competent citizens in various languages. This abstract provides a brief overview of the research and its findings, as well as presenting implications and recommendations for the development of multilingual learning programs in the future.